Pengaruh Cyberloafing Dan Disiplin Kerja Terhadap Kinerja Karyawan Rumah Sakit Natar Medika - Setyanto, Aldo Navela; Ribhan (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2024)
Cyberloafing and work discipline are often the causes of decreased employee performance. The purpose of this research is to partially analyze the influence of Cyberloafing and good work discipline on the performance of employees at Natar Medika Hospital located in Natar, South Lampung. The sample was 100 respondents who were employees of Natar Medika Hospital. Data analysis uses quantitative correlation using the t test. The results of this research show that Cyberloafing negatively effecting performance in significant way and work discipline positively effecting performance in significant way.